The Influence of Endorsement on Instagram toward Customer Behavior - Sutia, Sabar; Fahlevi, Mochammad; Rita; Rabiah, Arbi Siti; Adha, Shultonnyck (International Journal of Psychosocial Rehabilitation, 2020)
The appearance of social media has opened new opportunity for new brand to connect with customer directly and more organic. Companies currently have to evaluate and change their marketing strategies regarding advertising through social media. Marketing through influencers in social media is on the rise and is even one of the biggest marketing trends of 2017 (Glucksman, 2017). The development of digital technology has caused the majority of the world’s population to obtain access to the internet. Instagram is currently widely used for marketing a product. In this research, the researcher tried to analyze Yudha Refrizal as an influencer and its effect on consumer behavior. The results of the analysis provided information that the influence of Yudha Refrizal on consumer behavior had strong results, such as R value of 0.966 or 96.6% and coefficient values of 0.879 and significance 0,000. Thus, it gets a significant and positive effect.